Corporate Governance, Economic Entrenchment, and Growth - Morck, Randall; Wolfenzon, Daniel; Yeung, Bernard (Journal of Economic Literature, 2005)
Around the world, large corporations usually have controlling owners, who are usually very wealthy families. Outside the U.S. and the U.K., pyramidal control structures, cross shareholding and super voting rights are common. Using these devices, a family can control corporations without making a commensurate capital investment. In many countries, such families end up controlling considerable proportions of their countries'' economies. Three points emerge. First, at the firm level, these ownership structures vest dominant control rights with families who often have little real capital invested n creating agency and entrenchment problem simultaneously. In addition, controlling shareholders can divert corporate resources for private benefits using transactions within the pyramidal group. The result is a poor utilization of resources. At the economy level, extensive control of corporate assets by a few families distorts capital allocation and reduces the rate of innovation. The result is an economy-wide misallocation of resources, and slower economic growth.